Motivation of Farmers in Raising Bangkok Chickens in Unaaha Subdistrict, Konawe Regency - Hadini, Hairil A.; Sani, La Ode Arsad; Silondae, Ratna; Munadi, La Ode Muhammad (Pascasarjana Universitas Halu Oleo, 2024)
Motivation plays a crucial role in driving individuals to achieve goals and lead a fulfilling life. This study focuses on assessing the motivation levels of farmers engaged in raising Bangkok Chickens in Unaaha District, Konawe Regency. Conducted in March-April 2023, the research involved 30 farmers as respondents. Data collection utilized a questionnaire, and subsequent analysis was carried out descriptively. The findings revealed that 80% of Bangkok Chicken breeders fell within the motivated category, with the remaining 20% classified as less motivated. The primary motivations identified among farmers were entertainment (39%), economic factors (33%), and social aspects, which were comparatively lower (28%). This study provides insights into the diverse motivations driving farmers in the poultry industry, contributing to a better understanding of their practices and aspirations.